Average Lifespan Shortened due to Stroke in Canada: A Nationwide Descriptive Study From 1990 to 2015. Issue 2 (February 2021) - Pham, Truong-Minh; Thanh, Nguyen Xuan; Wasylak, Tracy; Hill, Michael D.; Jeerakathil, Thomas; Sikdar, Khokan C.; Kaposhi, Bethany; Shack, Lorraine; Cheung, Winson Y.
Abstract : Background and Purpose: There are challenges in comparability when using existing life lost measures to examine long-term trends in premature mortality. To address this important issue, we have developed a novel measure termed average lifespan shortened (ALSS). In the present study, we used the ALSS measure to describe temporal changes in premature mortality due to stroke in the Canadian population from 1990 to 2015. Methods: Mortality data for stroke were obtained from the World Health Organization mortality database. Years of life lost was calculated using Canadian life tables. ALSS was calculated as the ratio of years of life lost in relation to the expected lifespan. Results: Over a 25-year timeframe, the age-standardized rates adjusted to the World Standard Population for deaths from all strokes and stroke types substantially decreased in both sexes. The ALSS measure indicated that men who died of stroke lost 12.1% of their lifespan in 1990 and 11.4% in 2015, whereas these values among women were 11.1% and 10.0%, respectively. Patients with subarachnoid hemorrhagic stroke lost the largest portion whereby both sexes lost about one-third of their lifespan in 1990 and one-fourth in 2015. Men with intracerebral hemorrhagic stroke lost around 18% of their lifespan in 1990 and 14% in 2015 as compared to women who lost about 16% and 12% over the same timeframe. The loss of lifespan for patients with ischemic stroke and other stroke types combined was relatively stable at about 10% throughout the study period. Conclusions: Our study demonstrated a modest improvement in lifespan among patients with stroke in Canada between 1990 and 2015. Our novel ALSS measure provides intuitive interpretation of temporal changes in lifespan among patients with stroke and helps to enhance our understanding of the burden of strokes in the Canadian population. Abstract : Supplemental Digital Content is available in the text.